Sodium ion battery positive electrode sodium supplementing agent and preparation method and application thereof

By using sodium carbon-oxygen compounds and nanocarbon composites as the positive sodium supplementing agent of sodium ion batteries, the problems of high decomposition voltage and low decomposition capacity of existing sodium supplementing agents are solved, and the energy density and electrochemical performance of the battery are improved.

CN119627109APending Publication Date: 2025-03-14NINGBO RONBAY LITHIUM BATTERY MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411795517.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The current sodium ion battery positive sodium supplementation agent has the problems of high decomposition voltage and low decomposition capacity, resulting in easy damage to the battery module and reduced energy density.

Method used

The composite of carbon-oxygen compounds including sodium and nanocarbons is used as sodium supplementing agents, and prepared by basket milling and sand milling treatment. The D50 particle size is controlled to be 20-100 nm, the BET specific surface area is 30-200 m2/g, the Na element mass proportion is 20-30%, and the Na element distribution uniformity is ≥80%.

Benefits of technology

The decomposition voltage of sodium supplement agent is reduced and the decomposition capacity is improved, and the energy density and electrochemical performance of the battery are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627109A_ABST
    Figure CN119627109A_ABST
Patent Text Reader

Abstract

The invention provides a sodium ion battery positive electrode sodium supplementing agent and a preparation method and application thereof, and the sodium supplementing agent comprises a sodium carbon oxide compound and a nanocarbon compound; the decomposition voltage of the sodium supplementing agent is less than or equal to 4.3 V, and the decomposition capacity is greater than or equal to 320mAh / g. The sodium ion battery positive electrode sodium supplementing agent provided by the invention has the characteristics of relatively low decomposition voltage and relatively high decomposition capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a sodium ion battery positive electrode sodium supplement, in particular to a sodium ion battery positive electrode sodium supplement and a preparation method and application thereof, belonging to the field of new energy. Background Art

[0002] Sodium-ion batteries have attracted great attention as a promising large-scale energy storage material. During the initial operation of sodium-ion batteries, sodium ions in the battery are irreversibly consumed due to reasons such as the formation of SEI film, and the battery suffers irreversible capacity loss in the above process.

[0003] At present, in order to make up for the above capacity loss, additional sodium source can be provided to the battery by adding sodium supplement to the positive electrode material. During the initial operation, the sodium ions in the sodium supplement can escape from the positive electrode structure and form a stable SEI film at the negative electrode, which increases the active sodium retention rate of the positive electrode and reduces the capacity loss caused by the initial operation of the battery.

[0004] However, the current sodium supplement has the defects of high decomposition voltage and low decomposition capacity. When the decomposition voltage of the sodium supplement is high, the components in the battery are easily damaged by the high voltage; when the decomposition capacity of the sodium supplement is low, the sodium supplement needs to be added in a larger amount to be effective, and a larger addition will reduce the energy density of the battery.

[0005] Therefore, developing a positive electrode sodium supplement for sodium ion batteries with lower decomposition voltage and higher decomposition capacity has become a research direction in this field. Summary of the invention

[0006] The invention provides a sodium ion battery positive electrode sodium supplement, which has the characteristics of low decomposition voltage and high decomposition capacity.

[0007] The present invention also provides a positive electrode sheet, which has the characteristic of high energy density.

[0008] The present invention also provides a sodium ion battery, which has the characteristic of high energy density.

[0009] The present invention provides a sodium ion battery positive electrode sodium supplement, wherein the sodium supplement comprises sodium carbon oxides and nanocarbon;

[0010] The D50 particle size of the sodium supplement is 20-100 nm; the BET specific surface area is 30-200 m 2 / g;

[0011] The mass proportion of Na element on the surface of the sodium supplementer is 20-30%, and the uniformity of Na element distribution is ≥80%.

[0012] The sodium ion battery positive electrode sodium supplement as described above, wherein the D50 particle size of the sodium supplement is 50-70nm; the BET specific surface area is 80-150m 2 / g.

[0013] As described above, the sodium supplement for the positive electrode of the sodium ion battery, wherein the mass percentage of the nano-carbon in the sodium supplement is 2-20wt%.

[0014] The sodium ion battery positive electrode sodium supplement as described above, wherein the decomposition voltage of the sodium supplement is less than or equal to 4.3V, and the decomposition capacity is greater than or equal to 320mAh / g.

[0015] The sodium ion battery positive electrode sodium supplement as described above, wherein the chemical formula of the sodium carbon oxide compound is Na x C y O z , 2≤x≤4, 2≤y≤6, 4≤z≤6.

[0016] The sodium ion battery positive electrode sodium supplement as described above, wherein the nanocarbon is selected from at least one of Ketjen black, multi-walled carbon nanotubes, single-walled carbon nanotubes, conductive carbon black, Super P, carbon fiber, and graphene.

[0017] The sodium ion battery positive electrode sodium supplement as described above is prepared by a method comprising the following process:

[0018] The mixed system of the carbon oxide compound including sodium, nano-carbon and organic solvent is subjected to basket milling treatment and sand milling treatment in sequence to obtain the positive electrode sodium supplement agent for sodium ion battery;

[0019] The rotation speed of the basket mill treatment is 1000-1500rpm, the D50 of the particles in the basket mill treatment system is 0.3-1 micron, and the basket mill treatment is stopped; the rotation speed of the sand mill treatment is 1000-2000rpm, the D50 of the particles in the sand mill treatment system is 20-100nm, and the sand mill treatment is stopped.

[0020] The sodium ion battery positive electrode sodium supplement as described above, wherein the treatment system obtained by the sand grinding treatment is further subjected to a drying treatment; the treatment temperature of the drying treatment is 100-140° C., and the treatment time is 8-16 hours.

[0021] The present invention also provides a positive electrode sheet, comprising any one of the above-mentioned sodium supplement agents.

[0022] The present invention also provides a battery, comprising any one of the above-mentioned sodium supplement agents; and / or comprising the above-mentioned positive electrode sheet.

[0023] The sodium ion battery positive electrode sodium supplement provided by the present invention has the characteristics of low decomposition voltage and high decomposition capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is the SEM photo of sodium supplement L1;

[0025] Figure 2 This is the SEM photo of sodium supplement L6;

[0026] Figure 3 This is the SEM photo of sodium supplement M1;

[0027] Figure 4 This is the EDS test result of sodium supplement L1;

[0028] Figure 5 This is the EDS test result of sodium supplement M1;

[0029] Figure 6 is the charge and discharge curve of sodium supplement L1;

[0030] Figure 7 This is the charge and discharge curve of sodium supplement agent M1. DETAILED DESCRIPTION

[0031] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below. The specific implementation methods listed below are only for describing the principles and features of the present invention. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0032] The first aspect of the present invention provides a sodium ion battery positive electrode sodium supplement, the sodium supplement comprises a sodium carbon oxide and nanocarbon; the D50 particle size of the sodium supplement is 20-100nm; the BET specific surface area is 30-200m 2 / g; the mass proportion of Na element on the surface of the sodium supplementer is 20-30%, and the uniformity of Na element distribution is ≥80%.

[0033] The sodium ion battery positive electrode sodium supplement provided by the present invention can be used as an additive for the preparation of sodium ion batteries, and the sodium supplement includes sodium carbon oxides and nano-carbons. Further, the sodium supplement includes a composite of sodium carbon oxides and nano-carbons, wherein the composite of sodium carbon oxides and nano-carbons is a product obtained by combining sodium carbon oxides and nano-carbons.

[0034] Sodium carbon oxides refer to compounds including sodium, carbon and oxygen, and nanocarbons refer to carbon single substances with at least one dimension of the dispersed phase being less than 100 nm. The present invention does not limit the specific selection of sodium carbon oxides and nanocarbons, and compounds commonly used in the art can be used.

[0035] The positive electrode sodium supplement for sodium ion batteries provided by the present invention was subjected to EDS testing, and the EDS image showed that the mass proportion of the surface Na element of the sodium supplement was between 20-30%, which indicates that in the positive electrode sodium supplement for sodium ion batteries provided by the present invention, the composite of sodium oxalate and nano-carbon is highly uniform and has many binding sites.

[0036] The uniformity of the distribution of sodium in the sodium supplement is defined as 1-σ Na , where σ Na The standard deviation of manganese content measured at 10 random points in the precursor sample. The uniformity test of element distribution of the sodium supplementer showed that the uniformity of Na element distribution was ≥80%, which means that the Na element distribution on the surface of the sodium supplementer was relatively uniform.

[0037] The inventors have found that the positive electrode sodium supplement for sodium ion batteries provided by the present invention has the characteristic of a low decomposition voltage. The inventors speculate that the reason may be that nanocarbon can reduce the band gap width of sodium carbon oxides, thereby improving the electrochemical activity of sodium carbon oxides, so that the sodium ion battery provided by the present invention has a lower decomposition voltage. Furthermore, the positive electrode sodium supplement for sodium ion batteries provided by the present invention has the characteristic of a high decomposition capacity. The inventors speculate that the reason may be that the high electronic conductivity of the sodium supplement system reduces the decomposition voltage of the sodium supplement, and can exert a specific capacity close to the theoretical decomposition capacity.

[0038] The inventor further discovered that the reason why the sodium supplement with the above characteristics has the characteristics of lower boundary voltage and higher decomposition capacity may be that the carbon oxides of sodium and nano-carbon have suitable D50 particle size and BET specific surface area, and the sodium supplement also has suitable surface Na element mass ratio and Na element distribution uniformity, which makes the effective binding sites of the carbon oxides of sodium and nano-carbon higher, and increases the conductivity of the sodium supplement system, which helps nano-carbon reduce the band gap of the carbon oxides of sodium; further reduce its decomposition voltage and increase its decomposition capacity. Therefore, the above sodium supplement has a lower decomposition voltage and a larger decomposition capacity.

[0039] The sodium supplement provided by the invention has the characteristics of low decomposition voltage and high decomposition capacity.

[0040] Further, in one embodiment, the D50 particle size of the sodium ion battery positive electrode sodium supplement provided by the present invention is 50-70nm; the BET specific surface area is 80-150m 2 / g. Due to the appropriate particle size and specific surface area, the sodium supplement has the more prominent characteristics of low decomposition voltage and high decomposition capacity.

[0041] In one embodiment, the mass percentage of nano-carbon in the sodium supplement is 2-20wt%. The sodium supplement satisfying the above characteristics has a lower decomposition voltage and a larger decomposition capacity. Further, the mass percentage of nano-carbon in the sodium supplement is preferably 5-10%.

[0042] In one embodiment, the sodium supplement provided by the present invention has a decomposition voltage of less than or equal to 4.3 V and a decomposition capacity of greater than or equal to 320 mAh / g.

[0043] The present invention does not limit the combination mode of the sodium carbon oxide and the nanocarbon, as long as the decomposition voltage of the sodium supplement is less than or equal to 4.3V and the decomposition capacity is greater than or equal to 320mAh / g.

[0044] The sodium supplement provided by the present invention has a decomposition voltage of less than or equal to 4.3V and a decomposition capacity of greater than or equal to 320mAh / g. The decomposition voltage refers to the voltage at which the sodium supplement begins to decompose and release sodium ions. The smaller the decomposition voltage, the easier it is for the sodium supplement to decompose. The decomposition capacity refers to the charge capacity provided by the sodium supplement after decomposition. The larger the decomposition capacity, the more sodium ions can be released by the sodium supplement of the same mass.

[0045] In one embodiment, the chemical formula of the sodium carbon oxide is Na x C y O z , 2≤x≤4, 2≤y≤6, 4≤z≤6. Since the above sodium carbon oxides only produce sodium ions and carbon dioxide gas after decomposition, no other byproducts that have a negative impact on battery performance are produced and introduced into the battery, so the sodium supplement including such sodium carbon oxides has the more prominent feature of no impurities introduced.

[0046] Furthermore, in one embodiment, the sodium carbon oxide is selected from at least one of Na2C2O4, Na2C4O4, Na2C3O5, and Na4C6O6. The sodium supplement including the above sodium carbon oxide has a higher theoretical specific capacity.

[0047] Further, in one embodiment, the nanocarbon is selected from at least one of Ketjen black (KB), multi-walled carbon nanotubes (MWCNT), single-walled carbon nanotubes (SWNT), conductive carbon black, Super P (SP), carbon fiber, and graphene. The sodium supplement comprising the nanocarbon has a more prominent feature of low decomposition voltage due to the principle of high electronic conductivity.

[0048] In one embodiment, the sodium ion battery positive electrode sodium supplement provided by the present invention is prepared by a method comprising the following process:

[0049] The mixed system including sodium carbon oxide, nanocarbon and organic solvent is subjected to basket milling and sand milling in sequence to obtain a positive electrode sodium supplement for sodium ion batteries;

[0050] The rotation speed of the basket mill treatment is 1000-1500rpm, the D50 of the particles in the basket mill treatment system is 0.3-1 micron, and the basket mill treatment is stopped; the rotation speed of the sand mill treatment is 1000-2000rpm, the D50 of the particles in the sand mill treatment system is 20-100nm, and the sand mill treatment is stopped.

[0051] The solid content in the mixed system is 5-20wt%.

[0052] The basket milling process is to use a basket mill to treat a mixed system including sodium carbon oxides, nanocarbons and organic solvents. This process can reduce the particle size of sodium carbon oxides and nanocarbons, and make the substances in the mixed system evenly mixed. The speed of the basket milling process is 1000-1500rpm. When the D50 of the particles in the basket milling process is 0.3-1 micron, the basket milling process is stopped.

[0053] Sand milling is to use a sand mill to process the mixed system obtained by basket milling. This process can further reduce the particle size of sodium carbon oxides and nanocarbons, making the materials in the mixed system more evenly mixed. The speed of sand milling is 1000-2000rpm. When the D50 of the particles in the sand milling system is 20-100nm, the sand milling is stopped.

[0054] The organic solvent can make the nano-carbon and the carbon oxide of sodium disperse more evenly and achieve better combination effect. The present invention does not limit the type of organic solvent, as long as the requirement that the nano-carbon and the carbon oxide of sodium are not dissolved in the organic solvent is met. In one embodiment, the organic solvent is selected from at least one of ethanol, ether, and propanol.

[0055] In one embodiment, the solid content in the mixed system is 5-20 wt %. The mixed system with the above solid content helps the substances in the system to be more evenly dispersed, and the prepared sodium supplement has a lower decomposition voltage and a higher decomposition capacity.

[0056] Wet sand mills can produce finer abrasives and have higher sand milling efficiency; they can prevent material adhesion; and they can also reduce wear and heat. Basket milling and sand milling of a mixture of sodium carbon oxides and nanocarbons in an organic solvent can achieve uniform dispersion and mutual bonding of sodium carbon oxides and nanocarbons, which helps to increase the binding sites of sodium carbon oxides and nanocarbons, and make the ratio of the binding site volume of sodium carbon oxides and nanocarbons to the total volume of the sodium supplementer higher, so that the prepared sodium supplementer has a lower decomposition voltage and a higher decomposition capacity.

[0057] Furthermore, in one embodiment, the preparation process further comprises drying the treatment system obtained by sand milling; the treatment temperature of the drying treatment is 100-140° C., and the treatment time is 4-18 hours. Appropriate drying treatment conditions can fully volatilize the solvent in the treatment system obtained by sand milling, and the obtained sodium supplement has a higher purity.

[0058] A third aspect of the present invention provides a positive electrode sheet, which includes any one of the above-mentioned sodium supplement agents.

[0059] The positive electrode sheet of the present invention specifically includes a positive electrode current collector and a positive electrode active layer formed of a positive electrode active material and arranged on the surface of the positive electrode current collector.

[0060] When preparing the positive electrode sheet, for example, the sodium supplement provided by the present invention, the positive electrode active material and the binder can be dispersed in an appropriate amount of N-methylpyrrolidone (NMP) solvent, and fully stirred and mixed to form a uniform positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode current collector, and the positive electrode sheet is obtained after drying, rolling and cutting. In a specific embodiment, the positive electrode active layer includes 70-99wt% of the positive electrode active material, 0.5-15wt% of the conductive agent, and 0.5-15wt% of the binder according to the mass percentage, and further includes 80-98wt% of the positive electrode active material, 1-10wt% of the conductive agent, and 1-10wt% of the binder.

[0061] Among them, the material of the positive electrode current collector can be at least one of aluminum foil, carbon-coated aluminum foil, copper foil and nickel foil; the binder can be selected from at least one of fluorine-containing resin, polyether resin, cellulose type binder, polyacrylate type binder and polyimide.

[0062] Since the sodium supplement provided by the present invention has the characteristics of low decomposition voltage and high decomposition capacity, the positive electrode sheet provided by the present invention can provide a higher energy density.

[0063] A fourth aspect of the present invention provides a sodium ion battery, which comprises any one of the above sodium supplements, or comprises the above positive electrode sheet. This sodium ion battery has the characteristic of high energy density.

[0064] It is conceivable that the battery provided by the present invention includes, in addition to the above-mentioned positive electrode sheet, a negative electrode sheet, an electrolyte and a separator.

[0065] The present invention does not strictly limit the negative electrode active material in the negative electrode sheet, and can be at least one of the negative electrode active materials commonly used in sodium ion batteries, such as sodium sheets, graphite, hard carbon, soft carbon, mesophase carbon microspheres, silicon-based negative electrode materials (mainly including silicon oxide, silicon-carbon negative electrode), tin-based negative electrode materials (mainly including tin, tin alloys), etc.

[0066] The present invention does not strictly limit the choice of electrolyte, which may include one or more of the solvents commonly used in sodium ion battery electrolytes, for example, at least one of the solutions of propylene carbonate and / or ethylene carbonate of NaPF6 and / or NaClO4.

[0067] The present invention does not strictly limit the material selection of the diaphragm, and it can be a diaphragm material commonly used in current sodium ion batteries, such as at least one selected from polypropylene, polyethylene, and glass fiber.

[0068] In one embodiment, a sodium ion battery can be prepared by the following steps: a sodium supplement, a positive electrode conductive additive, and a positive electrode binder are evenly mixed in an organic solvent NMP, applied to a positive electrode collector and dried to obtain a pretreated positive electrode sheet, and a sodium sheet, a diaphragm, an electrolyte, and a positive electrode sheet are placed in a buckle battery shell in sequence, and pressurized to form a buckle battery.

[0069] The following examples further illustrate the sodium ion battery positive electrode sodium supplement provided by the present invention and its preparation method and application.

[0070] Example 1

[0071] 1) Dispersing 200 g of commercial sodium oxalate and 10 g of SP in 2 L of anhydrous ethanol, wherein, by mass, sodium oxalate:SP:ethanol=1:0.05:10, to obtain a mixed system;

[0072] 2) The mixed system is first subjected to basket milling treatment at a rotation speed of 1200 rpm in a basket mill. When the particles in the basket milling treatment system meet the D50 of 0.6 microns, the basket milling treatment is completed to obtain a basket milling system;

[0073] 3) The basket mill system was sand-milled at 1300 rpm in a sand mill. When the particles in the sand-milled system met the D50 of 50 nm, the sand-milling treatment was completed, the reaction system was filtered, and the solid part was dried at 120° C. for 12 h to obtain 210 g of sodium supplement L1.

[0074] Since the mass of the nano-carbon is 10 g and the mass of the sodium supplement is 210 g, the mass percentage of the nano-carbon in the sodium supplement is: 10÷210×100%=4.76%.

[0075] Example 2

[0076] This embodiment is substantially the same as embodiment 1, except that the same mass of Na2C3O5 is used to replace commercial sodium oxalate;

[0077] 210g of sodium supplement L2 was obtained.

[0078] Since the mass of the nano-carbon is 10 g and the mass of the sodium supplement is 210 g, the mass percentage of the nano-carbon in the sodium supplement is: 10÷210×100%=4.76%.

[0079] Example 3

[0080] This embodiment is substantially the same as embodiment 1, except that Ketjen black (KB) of the same mass is used instead of SP;

[0081] 210g of sodium supplement L3 was obtained.

[0082] Since the mass of the nano-carbon is 10 g and the mass of the sodium supplement is 210 g, the mass percentage of the nano-carbon in the sodium supplement is: 10÷210×100%=4.76%.

[0083] Example 4

[0084] This example is basically the same as Example 1, except that the mass of SP is 2 g, and 200 g of commercial sodium oxalate is reduced to 98 g;

[0085] 100g of sodium supplement L4 was obtained.

[0086] Since the mass of the nano-carbon is 2 g and the mass of the sodium supplement is 100 g, the mass percentage of the nano-carbon in the sodium supplement is: 2÷100×100%=2.00%.

[0087] Example 5

[0088] This embodiment is basically the same as embodiment 1, except that the mass of SP is 70 g;

[0089] 270g of sodium supplement L5 was obtained.

[0090] Since the mass of the nano-carbon is 70 g and the mass of the sodium supplement is 270 g, the mass percentage of the nano-carbon to the sodium supplement is: 70÷270×100%=25.93%.

[0091] Example 6-Example 17 respectively prepared sodium supplements L6-L17, and the specific implementation methods are shown in Table 1. The unlisted parts are the same as Example 1.

[0092] Table 1 Specific implementation methods of Examples 6-17

[0093]

[0094] Comparative Example 1

[0095] 200 g of commercial sodium oxalate was dissolved in 6 L of water to obtain a mixed solution. 2 g of KB was dispersed in the mixed solution, and then the mixed solution was transferred to 12 L of ethanol to allow the mixed solution to recrystallize. The reaction system was filtered to obtain the solid part, which was dried at 120° C. for 12 h to obtain 202 g of sodium supplement M1.

[0096] Since the mass of the nano-carbon is 2 g and the mass of the sodium supplement is 202 g, the mass percentage of the nano-carbon in the sodium supplement is: 2÷202×100%=0.99%.

[0097] Comparative Example 2

[0098] This comparative example is basically the same as Example 1, except that the basket mill system obtained in step 2) is filtered, and the solid part is dried at 120° C. for 12 h to obtain 210 g of sodium supplement M2.

[0099] Since the mass of the nano-carbon is 10 g and the mass of the sodium supplement is 210 g, the mass percentage of the nano-carbon in the sodium supplement is: 10÷210×100%=4.76%.

[0100] Comparative Example 3

[0101] This comparative example is basically the same as Example 1, except that the mixed system in step 1) does not contain ethanol, that is, the remaining steps are performed on the mixed system composed of commercial sodium oxalate and SP (the filtration step is omitted accordingly) to prepare 210g of sodium supplement M3.

[0102] Since the mass of the nano-carbon is 10 g and the mass of the sodium supplement is 210 g, the mass percentage of the nano-carbon in the sodium supplement is: 10÷210×100%=4.76%.

[0103] Comparative Example 4

[0104] 1) Disperse 200 g of Na4C6O6 in 2 L of ether to obtain a mixed system;

[0105] 2) The mixed system is first subjected to basket milling treatment at a rotation speed of 1200 rpm in a basket mill. When the particles in the basket milling treatment system meet the D50 of 0.6 microns, the basket milling treatment is completed to obtain a basket milling system;

[0106] 3) The basket mill system was sand-milled in a sand mill at 1300 rpm. When the particles in the sand-milled system met the D50 of 50 nm, the sand-milling treatment was completed, the reaction system was filtered, and the solid part was dried at 120° C. for 12 h to obtain the sodium supplement M4.

[0107] Comparative Example 5

[0108] 1) Dispersing 200 g Na2C4O4 and 3 g MWCNT in 3 L acetone to obtain a mixed system;

[0109] 2) The mixed system was first subjected to basket milling treatment at a speed of 1200 rpm in a basket mill. When the particles in the basket milling treatment system met the D50 of 0.6 microns, the basket milling treatment was completed, the reaction system was filtered, and the solid part was dried at 120° C. for 12 hours to obtain 203 g of sodium supplement M5.

[0110] Since the mass of the nano-carbon is 3 g and the mass of the sodium supplement is 203 g, the mass percentage of the nano-carbon in the sodium supplement is: 3÷203×100%=1.48%.

[0111] Comparative Example 6

[0112] This comparative example is basically the same as Example 1, except that in step 3), when the particles in the sand milling system satisfy the D50 of 200 nm, the sand milling process is terminated to obtain 210 g of sodium supplement M6.

[0113] Since the mass of the nano-carbon is 10 g and the mass of the sodium supplement is 210 g, the mass percentage of the nano-carbon in the sodium supplement is: 10÷210×100%=4.76%.

[0114] Test Example 1

[0115] Take the SEM image of sodium supplement L1, see Figure 1 ;

[0116] Depend on Figure 1 It can be seen that L1 has a smaller particle size as it is nano-scale, and the contact area between sodium oxalate and SP is relatively large.

[0117] Take the SEM image of sodium supplement L6, see Figure 2 ;

[0118] Depend on Figure 1 It can be seen that L6 is a nano-scale particle with a small particle size, and the contact area between sodium oxalate and SP is relatively large.

[0119] Take the SEM image of sodium supplement M1, see Figure 3 ;

[0120] Depend on Figure 3 It can be seen that the sodium oxalate in M1 is micron-sized particles, and the distribution uniformity of KB and sodium oxalate on the surface of the composite material is relatively high.

[0121] Test Example 2

[0122] EDS test was performed on sodium supplement L1, and the results are shown in Figure 4 ;

[0123] Depend on Figure 4 It can be seen that the mass proportion of Na element on the surface of sodium supplement L1 is 20.7%;

[0124] The sodium supplement M1 was tested by EDS, and the results are shown in Figure 5 ;

[0125] Depend on Figure 5 It can be seen that the surface mass proportion of Na element in sodium supplement M1 is 1.3%, indicating that the surface mass proportion of Na element in the sample prepared by recrystallization method is low due to the large particle size and poor distribution uniformity of nanocarbon.

[0126] Test Example 3

[0127] The surface Na element distribution uniformity test was carried out on each sodium supplement sample. The test method was: randomly select 10 points from each sample, test the Na element content, and calculate the Na element standard deviation and uniformity of the corresponding sample.

[0128] The test results are shown in Table 2.

[0129] Table 2 Element distribution uniformity test

[0130]

[0131]

[0132] It can be seen from Table 2 that the sodium supplement prepared by the preparation method provided by the present invention has a higher surface distribution uniformity of the Na element.

[0133] It can be seen from the comparative example data that the uniformity of the Na element in the sodium supplement prepared in each comparative example is low.

[0134] Test Example 3

[0135] The D50 particle size and BET specific surface area of ​​each sodium supplement were measured respectively, and the mass percentage of the surface Na element was measured by EDS.

[0136] The measurement results are shown in Table 3.

[0137] Table 3 Physical characteristics test results

[0138]

[0139] It can be seen from Table 3 that, compared with the samples prepared in the comparative examples, the sodium supplement prepared in the embodiments of the present invention has a smaller D50 particle size and a larger BET specific surface area.

[0140] Test Example 4

[0141] 10g of each sodium supplement was mixed with a binder and a dispersant to prepare a positive electrode slurry, which was then coated on a carbon-coated aluminum foil and dried in a vacuum at 120°C for 12h to obtain a positive electrode sheet. The coating thickness of the positive electrode slurry was 150 microns and the surface density was 3mg / cm 2.

[0142] The detailed formula of the positive electrode slurry prepared with each sodium supplement is shown in Table 4.

[0143] Table 4 Positive electrode slurry formula

[0144]

[0145]

[0146] The sodium sheet negative electrode, glass fiber separator, NaPF6 electrolyte and positive electrode sheet were assembled into a button half-cell. The voltage window was 2.5-4.5V, the nominal capacity was 400mAh / g, the temperature was 40°C, and the decomposition capacity and average charging voltage (i.e., decomposition voltage) of the sodium supplement at 0.1C constant current plus constant voltage (constant voltage to 0.01C) were measured.

[0147] The test results are shown in Table 5, where the charge and discharge curves of the sodium supplement L1 are shown in Figure 6 The charge and discharge curve of sodium supplement M1 is shown in Figure 7 .

[0148] Table 5 Electrochemical characteristics test results

[0149]

[0150]

[0151] It can be seen from Table 5 that the sodium supplement provided by the present invention has a relatively high decomposition capacity and a relatively low decomposition voltage. In comparison, the sodium supplement prepared in each comparative example has a relatively high decomposition voltage and a relatively low decomposition capacity.

[0152] contrast Figure 6 and Figure 7 It can be seen that the decomposition voltage of sample M1 is significantly higher than that of sample L1 and the decomposition capacity is significantly lower than that of sample L1, which indicates that the sodium supplement provided by the embodiment of the present invention has the characteristics of lower decomposition voltage and higher decomposition capacity.

[0153] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A sodium ion battery positive electrode sodium supplement, characterized in that: The sodium supplement comprises sodium carbon oxides and nanocarbon; The D50 particle size of the sodium supplement is 20-100 nm; the BET specific surface area is 30-200 m 2 / g; The mass proportion of Na element on the surface of the sodium supplementer is 20-30%, and the uniformity of Na element distribution is ≥80%.

2. The sodium supplement according to claim 1, characterized in that The D50 particle size of the sodium supplement is 50-70 nm; the BET specific surface area is 80-150 m 2 / g.

3. The sodium supplement according to claim 1 or 2, characterized in that The mass percentage of the nano-carbon in the sodium supplement is 2-20wt%.

4. The sodium supplement according to any one of claims 1 to 3, characterized in that The decomposition voltage of the sodium supplement is less than or equal to 4.3V, and the decomposition capacity is greater than or equal to 320mAh / g.

5. The sodium supplement according to any one of claims 1 to 4, characterized in that The chemical formula of the sodium carbon oxide is Na x C y O z , 2≤x≤4, 2≤y≤6, 4≤z≤6.

6. The sodium supplement according to any one of claims 1 to 5, characterized in that The nanocarbon is selected from at least one of Ketjen black, multi-walled carbon nanotubes, single-walled carbon nanotubes, conductive carbon black, Super P, carbon fiber, and graphene.

7. The sodium supplement according to any one of claims 1 to 6, characterized in that It is prepared by a method comprising the following steps: The mixed system of the carbon oxide compound including sodium, nanocarbon and organic solvent is subjected to basket milling treatment and sand milling treatment in sequence to obtain the positive electrode sodium supplement for sodium ion battery; The rotation speed of the basket mill treatment is 1000-1500rpm, the D50 of the particles in the basket mill treatment system is 0.3-1 micron, and the basket mill treatment is stopped; the rotation speed of the sand mill treatment is 1000-2000rpm, the D50 of the particles in the sand mill treatment system is 20-100nm, and the sand mill treatment is stopped.

8. The sodium supplement according to claim 7, characterized in that The process also includes drying the treated system obtained by the sand grinding process; The drying process has a treatment temperature of 100-140° C. and a treatment time of 4-18 hours.

9. A positive electrode sheet, characterized in that: The invention comprises the sodium supplement according to any one of claims 1 to 8.

10. A sodium ion battery, characterized in that: The sodium supplement according to any one of claims 1 to 8; and / or Including the positive electrode sheet as described in claim 9.